Accelerating Photocatalytic Hydrogen Production and Pollutant Degradation by Functionalizing g-C3N4 With SnO2 - Zada, Amir; Khan, Muhammad; Qureshi, Muhammad Nasimullah; Liu, Shu-yuan; Wang, Ruidan (Frontiers in Chemistry, 2020)
Energy crises and environmental pollution serious threat to the modern society. To overcome these problems, graphitic carbon nitride (g-C3N4) nanosheets were fabricated and functionalized with SnO2 nanoparticles to produce H2 from water and degrade 2-chlorophenol under visible light irradiation. The fabricated samples showed enhanced photocatalytic activities for both H2 evolution and pollutant degradation as compare to bare g-C3N4 and SnO2. These enhanced photoactivities are attributed to the better charge separation as the excited electrons transfer from g-C3N4 to the conduction band of SnO2. This enhanced charge separation has been confirmed from photoluminescence spectra, steady state surface photovoltage spectroscopic measurement and formed hydroxyl radicals. It is believed that this work will provide a feasible route to synthesize photocatalysts for improved energy production and environmental purification.